(untitled) (Research, Society and Development, 2022)
Introduction: The evaluation of the microbiological quality of water based on indicators is important due to the impossibility of identifying all microorganisms present. Based on this, the objective of this work is to highlight the main conditions of water for public supply in Brazil. Methodology: This is an integrative literature review, based on a qualitative and descriptive data research. A search was carried out in LILACS databases and CAPES journals portal with the descriptors quality (quality), water (water) and public schools (public schools). After using inclusion/exclusion criteria, the final sample of the integrative review was composed of 8 scientific articles. Results: Contaminated water is capable of transmitting infectious agents or substances capable of harming human health, according to the World Health Organization, about 80% of the diseases that occur in developing countries are transmitted by contaminated water and it is estimated that in the world more than two million people a year die from waterborne diseases. Final considerations: Monitoring the quality of water intended for human consumption by the population becomes essential, as it prevents the appearance of various diseases in humans, helps in the diagnosis of the main forms of contamination and indicates a set of practices for managing natural resources that allow pollution control and an increase in the quality of life for users of this water.